Penggunaan Standar Bumbu Masakan Lauk Hewani dan Nabati di RSUD Panembahan Senopati Bantul Yogyakarta - Kukuh Probo Sukmawati; Setyowati Setyowati; Th Ninuk Sri Hartini (JURNAL NUTRISIA, 2017)
Background: Using of herbs and spices greatly affect the taste of foods, although the ingredients used are the same, different formulations of herbs will produce different flavors. Standardized seasonings are needed to produce a relatively similar food taste. Objective: The research aims to determine the use of herbs in animal and plant proteins. Method: This research was an observational research with cross sectional approach at PanembahanSenopati Hospital Bantul. The objects of this research were standardized seasonings inanimal and plant proteinsin the menu cycle of 10 days in Juny 2015. The data were analyzed descriptively and presented in tabular form and textural. Result: Standardized Seasonings in animal protein were B for satay and C for semur. Standardized seasonings in plant protein were B for bali, terik, rujak and D for bacem. The percentage of the use of seasoning than standardized seasoning for satay (148,7%), bali (130,3%), rujak(372%),for semur, terik and bacem the conformity are not not known because the standardized seasonings unwritten. The conformity of ingredient herbskind for satay (66,7%), semur (100%), bali (54,5%), rujak (50%), bacem (100%) and terik (100%). Conclusion:The conformity of herbs weight foranimal protein (124,3%) and plant protein (175,5%). The conformity of ingredient herbskind for animal protein (83,3%) and plant protein (76,1%). Standardized seasonings used were B, C and D. Keywords: standardized seasonings, animal protein, plant protein